Arbitration In Legal Remediesn Against Dispute Resolution Construction Service Contract - Safnul, Dody (Legalpreneur Journal, 2024)
The purpose of this research is to find out what are the advantages and deficiencies in problem solving through arbitration and how the process dispute resolution through arbitration in construction contract disputes. By using research methods juridical normative, it can be concluded, that: 1. Arbitration is the way settlement of a civil dispute in outside the general court based on arbitration agreements made written by the parties to the dispute. 2. The existence of a written agreement negates the right of the parties to apply resolution of disputes or disagreements what's included in the agreement state court.